2009
DOI: 10.1021/jf9009153
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Chinese Star Anise from Japanese Star Anise Using Thermal Desorption−Gas Chromatography−Mass Spectrometry

Abstract: The volatile compounds from the pericarps of Illicium anisatum L., Illicium brevistylum A.C.Sm., Illicium griffithii Hook.f. & Thomson, Illicium henryi Diels, Illicium lanceolatum A.C.Sm., Illicium majus Hook.f. & Thomson, Illicium micranthum Dunn, and Illicium verum Hook.f. were examined by thermal desorption-gas chromatography-mass spectrometry (TD-GC-MS). The volatiles desorbed from the pericarps of I. verum (Chinese star anise), the species traded for culinary purposes, were generally characterized by a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 22 publications
5
36
0
1
Order By: Relevance
“…methoxyeugenol, in which the hydroxyl group on the benzene ring is substituted with a dimethylallyl group, are found as major constituents in a few plant species, including Illicium anisatum and Illicium verum (Howes et al 2009;Koeduka et al 2014), with the apparent function of strongly deterring oviposition by mites. The biosynthesis of these O-prenylated phenylpropenes is not yet well understood, since no phenylpropene-specific prenyltransferases have yet been characterized.…”
Section: Prenyltransferases O-prenylated Phenylpropenes Such As Odimmentioning
confidence: 99%
“…methoxyeugenol, in which the hydroxyl group on the benzene ring is substituted with a dimethylallyl group, are found as major constituents in a few plant species, including Illicium anisatum and Illicium verum (Howes et al 2009;Koeduka et al 2014), with the apparent function of strongly deterring oviposition by mites. The biosynthesis of these O-prenylated phenylpropenes is not yet well understood, since no phenylpropene-specific prenyltransferases have yet been characterized.…”
Section: Prenyltransferases O-prenylated Phenylpropenes Such As Odimmentioning
confidence: 99%
“…In contrast, the (E)-anethole content of I. anisatum is less than 3.0% (Cook and Howard, 1966;Wichtl, 2004). In addition, the volatiles desorbed from the pericarps of the toxic Japanese star anise were characterized by the presence of asaricin, methoxyeugenol, and two other eugenol derivatives, none of which were detected in any of the other species examined (Howes et al, 2009). …”
Section: Synonyms For Star Anisementioning
confidence: 99%
“…This is the first time to report the composition of the essential oil derived from I. henryi leaves. However, the essential oil of I. henryi fruits contained limonene (12.4 -32.8 %), caryophyllene (1.5 -8.5 %), safrole (0.4 -2.7 %) and 1, 8-cineole (1.2 -2.1 %) [13].…”
Section: Discussionmentioning
confidence: 98%
“…In the previous phytochemical investigations, various sesquiterpene lactones, lignans, flavonoids, triterpenoids, and prenylated C6-C3 compounds have been isolated and identified from the plant [10][11][12]. Chemical composition of the essential oil of I. henryi fruits has been analyzed previously [13]. However, a literature survey has shown that there is no report on chemical composition and larvicidal activity of the essential oil of I. henryi leaves against mosquitoes, thus we decided to investigate chemical composition and larvicidal activity of the essential oil of I. henryi leaves against the Asian tiger mosquito.…”
Section: Introductionmentioning
confidence: 99%